Coordination chemistry-- XIV : plenary lectures presented at the 14th International Conference on Coordination Chemistry held at Toronto, Canada 22-28 June 1972 - Lever, A. B. P. (Alfred Beverley Philip) (Butterworths, 1973)
Coordination Chemistry-XIV provides information pertinent to the fundamental characteristics and synthesis of coordination compounds. This book discusses the importance of undertaking accurate X-ray analysis of a wide-ranging series of complexes in order to derive more secure theoretical correlations. Organized into 13 chapters, this book begins with an overview of the properties of alkyl and aryl derivatives of transition elements. This text then describes the two methods that lead to transition metal complexes of carborane ligands, namely, polyhedral expansion and polyhedral contraction. Ot.